Key Factors Influencing High Sweet Beverage Consumption During Complementary Feeding Period - Ardiningsih, Eka Setya; Agushybana, Farid; Shaluhiyah, Zahroh (Universitas Airlangga, 2025)
Sweet beverages consumption during complementary feeding period is a major contributor to the increased risk of obesity and degenerative diseases in the future. Indonesia ranks third in Southeast Asia for sweet beverage consumption, with Central Java Province having the highest rate of fruit juice consumption during complementary feeding period (55.4%). An in-depth understanding of maternal characteristics is essential to formulate effective health promotion strategies to reduce sweet beverage consumption among children aged 6-23 months. Objective: This study aims to analyze the factors associated with sweet beverage consumption during complementary feeding period in Semarang Regency. Methods: This quantitative research uses a cross-sectional approach with 244 mothers of children aged 6-23 months in Semarang Regency. Univariate analysis was conducted using frequency distribution, while multivariate analysis was conducted using logistic regression tests (p<0.05). Results: The percentage of high sweet beverage consumption among children aged 6-23 months in Semarang Regency was 63.93%. Lower maternal education (p=0.047), increasing family income (p=0.000), older child age (p=0.002), higher support from health cadres (p=0.030), and greater household food availability (p=0.000) were associated with a higher odds of sweet beverage consumption during complementary feeding. Conversely, healthy children (p=0.000) and greater access to information through social media (p=0.009) were associated with a lower likelihood of sweet beverage consumption during this period. Conclusion: Factors influencing sweet beverage consumption during complementary feeding include maternal education level, child health status, family income, child age, support from health cadres, access to information through social media, and household food availability.